(untitled) (Indian Journal of Chemistry (IJC), 2025)
Cyclic Voltammetry (CV) is an electro analytical technique that gives information about the redox behavior of the analyte at a particular interface. Conducting polymers (CPs) are much explored sensor materials due to their unique properties like, tunable conductivity, structural versatility, stability and multiple synthetic pathways. In the present work investigations on the sensing ability of neat copolymer (Py-NVK) and ZnO nanocomposite (Py-NVK_ZnO) for 6-Thioguanine (6-TG) anti-cancer drug molecule through the Cyclic Voltammetry method have been reported. The investigation revealed that the ZnO nanocomposite is better sensor material in terms of current-voltage for the detection of 6-Thioguanine anti-cancer drug molecule in comparison to neat copolymer.